Praktik Jual Beli Multi Level Marketing Oriflame Perspektif Maqāṣid al-Syarī‘ah dan Fatwa DSN MUI No 75 Tahun 2009 - Firnanda, Dhea; Munna, Nurul Isna Faizatul; Sujianto, Agus Eko; Ni’mah, Zulfatun (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
The proliferation of scams disguised as Multi-Level Marketing (MLM) in Indonesia has raised public doubts about the legitimacy of MLM practices, including Oriflame, from the perspective of Islamic law. This indicates the need for a deeper study to assess the compatibility of Oriflame's MLM business mechanism with maqasid al-syariah and Fatwa DSN MUI No. 75 of 2009. This article is composed using a qualitative approach involving in-depth interviews and observations. Based on the research conducted, the mechanism of Oriflame's MLM practice begins with registering as an Oriflame reseller, promoting Oriflame products through social media, recruiting members or resellers, and developing downlines through training and sales tools. Oriflame's MLM practice involves reseller registration, product promotion via social media, member recruitment, and downline development through training. This system is halal and compliant with Sharia because it fulfills the maqasid syariah (hifz ad-din, al-nafs, al-aql, al-nasl, al-mal). In accordance with MUI Fatwa No. 75/2009, it meets 12 Sharia requirements, including real sale objects, halal certification, transactions without fraud/fixed prices, commissions from real sales/recruitment without ighra'/coercion, unpaid recruitment, downline development, and not being a money game.